Discursively constituted experience, or experience as reply: A rejoinder. (February 2013) - Haye, Andrés; Larrain, Antonia
The goal of the paper is to briefly sketch a theoretical proposal about the role played by discourse in the texture and texturing of lived experience. Inspired by the work of Bakhtin, we develop implications of concepts of inner speech, dialogicality, and specially outsideness, disputing the idea that phenomenological approaches are well equipped to account for human experience. The main argument is that so-called "immediate" experience is discursively mediated and, as such, is constituted by a dialogical dynamic of co-affection. We raise the idea that the streams of experience consist in social and psychological movements of reply.